Activity enhancement of layered cobalt hydroxide nanocones by tuning interlayer spacing and phosphidation for electrocatalytic water oxidation in neutral solutions 1. Issue 7 (28th May 2019) - Qin, Ruinan; Wan, Hao; Liu, Xiaohe; Chen, Gen; Zhang, Ning; Ma, Renzhi; Qiu, Guanzhou
Abstract : We explored the electrocatalytic performance of cobalt hydroxide nanocones in neutral solutions via tuning the interlayer spacing and phosphidation. Abstract : Due to the low cost, abundant reserves and redox-active features, electrocatalysts based on 3 d transition metals have been thoroughly evaluated and are considered promising candidates to the current commercial noble metal-based materials. Designing elaborate structures and favorable phase composition is regarded as effective to improve the activity in electrocatalysis. Herein, three kinds of layered cobalt hydroxide nanocones (NCs) with tunable interlayer spacing determined by the intercalated anion species were prepared. Because of the larger interlayer spacing which might be beneficial for faster mass transfer, dodecyl sulfate (DS − ) ion-intercalated layered cobalt hydroxide NCs yielded current densities of 5 and 10.65 mA cm −2 at overpotentials of 0.50 and 0.57 V, respectively, in the electrolytic oxygen evolution reaction (OER) in a neutral phosphate buffer solution (PBS); thus, they surpassed their counterparts with decreased layer distances induced by intercalated acetate (CH3 COO − ) or nitrate (NO3 − ) anions. When a further phosphidation treatment was adopted on NO3 − -intercalated cobalt hydroxide NCs, a cobalt phosphide (CoP) product with well-maintained conical morphology was obtained, which reduced the overpotential of ∼20 mV to reach the anodic exchange current density of 5 mA cm −2 . The activity enhancement induced by the tuning of interlayer spacing and phosphidation offers great promise for developing high-activity catalysts by rationally designing phase structure and composition for electrochemical energy conversion.